2016
DOI: 10.1371/journal.pone.0151397
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin Attenuates Synaptic Loss and Cognitive Deficits in an Aβ1–42-Induced Mouse Model of Alzheimer’s Disease

Abstract: Synaptic loss induced by beta-amyloid (Aβ) plays a critical role in the pathophysiology of Alzheimer’s disease (AD), but the mechanisms underlying this process remain unknown. In this study, we found that oridonin (Ori) rescued synaptic loss induced by Aβ1–42 in vivo and in vitro and attenuated the alterations in dendritic structure and spine density observed in the hippocampus of AD mice. In addition, Ori increased the expression of PSD-95 and synaptophysin and promoted mitochondrial activity in the synaptoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…Golgi staining was performed using an FD Rapid GolgiStain Kit (FD Neurotechnologies, Columbia, MD, USA) as previously described (Wang et al ., ). Briefly, brain tissues were immersed in impregnation solution consisting equal volumes of Solutions A and B for 2 weeks and then removed to Solution C for 3 days at room temperature in the dark.…”
Section: Methodsmentioning
confidence: 97%
“…Golgi staining was performed using an FD Rapid GolgiStain Kit (FD Neurotechnologies, Columbia, MD, USA) as previously described (Wang et al ., ). Briefly, brain tissues were immersed in impregnation solution consisting equal volumes of Solutions A and B for 2 weeks and then removed to Solution C for 3 days at room temperature in the dark.…”
Section: Methodsmentioning
confidence: 97%
“…The dose‐response curve of ORI was not investigated in our study, and thus we can not confirm the optimal dose of ORI for the treatment of sepsis. In our pilot study, sepsis mice were initially treated with ORI at 10 mg/kg which is the most common dose used in available studies [27]. However, the alanine aminotransferase further increased in sepsis mice after ORI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that neurotoxicity and synaptic dysfunction were alleviated with the administration of Ori in Alzheimer's disease mice. 34,50 Synaptic loss is believed to be the basis of cognitive impairment in the MHE. 51 We further confirmed the effect of Ori on the synaptic formation in vivo.…”
Section: Ori Prevents Synaptic Loss In Mhe Ratsmentioning
confidence: 99%
“…[30][31][32] Also, some studies found the impaired behaviour is significantly restored by Ori treatment. 33 Moreover, it has demonstrated that Ori can alleviate neurotoxicity and synaptic dysfunction in AD mice, 34 which means that Ori has the potential application against neurodegenerative disorders. Furthermore, a few studies have investigated that Ori could protect against diabetic nephropathy rats (DN).…”
Section: Introductionmentioning
confidence: 99%